Pengaruh Presiden Joko Widodo pada Penguatan Peran Diplomasi Ekonomi di Indonesia - Jhon Maxwell Yosua Pattinussa (Cenderawasih University, 2021)
The interactions between countries today are almost based on the interests of capital accumulation, particularly with the increase in new regionalism worldwide as if forcing the world’s nations to join or be left behind. Indonesia also encounters such circumstances and should respond to new challenges in global politics by taking a free and active stance using economic diplomacy as one of its main instruments. This article, using individual-level analysis, attempts to explain how President Joko Widodo strongly influences the increasing role of economic diplomacy. It also provides an overview of the relationship between political personality and the perception of President Widodo with economic diplomacy by adopting the rational actor model-foreign policy decision-making process. This article identified four critical things in strengthening the role of economic diplomacy for Indonesia: 1) changing interests in the reality of modern state interactions; 2) the possibility of taking policy alternatives; 3) individual analysis (leader) in seeing the risks and opportunities; 4) decision-making by the President. KEYWORDSDiplomacy; Indonesia; International Politics; Joko Widodo